Determination of ternary mixtures of dextromethorphan hydrobromide, pseudoephedrine hydrochloride and triprolidine hydrochloride in syrups by partial least-squares multivartate calibration - Donmez, Ozlem Aksu; Bozdogan, Abdurrezzak; Kunt, Gonul (WALTER DE GRUYTER GMBH, 2007)
PLS-2, a partial least-squares multivariate calibration, was used for the determination of dextromethorphan hydrobromide (DEX), pseudoephedrine hydrochloride (PSE) and triprolidine hydrochloride (TRP) in syrup samples. The method allows the simultaneous quantification of the analytes that the closely overlapping spectral bands are not efficiently solved. The calibration set consisting of 27 samples with 60, 80, 100 mu g mL(-1) of DEX, 180, 240, 300 mu g mL(-1) of PSE and 8,10,12 mu g mL(-1) of TRP was used for calibration matrix. The absorbances were recorded between 230 and 320 nm every 5 nm. The accuracy and precision of the method have been determined and the method has been validated by synthetic mixtures.
Keywords: dextromethorphan hydrobromide; pseudoephedrine hydrochloride; triprolidine hydrochloride; multivariate calibration; SPECTROPHOTOMETRIC CALIBRATION; ACETAMINOPHEN; REGRESSION; CAFFEINE; TABLETS; SPECTRA; MALEATE; Chemistry